COMBINING THE CONCEPTS OF BENCHMARKING AND MATRIX GAME IN MARKETING (RE)POSITIONING OF SEAPORTS - Sekularac-Ivošević, Senka; Bauk, Sanja; Gligorijević, Mirjana (Promet - Traffic&Transportation, 2013)
This paper considers the effects of combination of two different approaches in developing seaports positioning strategy. The first one is based on comparing the most important quantitative and qualitative seaports choice criteria by benchmarking method. Benchmarking has been used in creating the appropriate model for efficient marketing positioning of Aegean, Adriatic and Black Sea seaports. The criteria that describe the degree of these seaports competitiveness are chosen upon the investigation of ports customers’ preferences. The second employed approach based on matrix game concept has been used for the purpose of optimal repositioning of the ports. Though, nine selected ports’ functions are treated in a way that they are divided into two sets: one composed of the functions which are to be developed, and the other consisted of the functions for which it is expected to be suppressed in the future. According to the numerically obtained results the ports are repositioned, and corresponding explanations are given in the marketing manner. The mixture of these two concepts should contribute to the review of the state of these business systems and their images at the market, as well as to open prospective toward finding out the ways of creating and maintaining their competitive advantages.